A qualitative study of midlife women with type 2 diabetes in the UK: Exploring the impact of diabetes on their well-being - Natalia Ioannou; Iliatha Papachristou Nadal (PLoS ONE, 2026)
Background and aims Type 2 Diabetes mellitus (T2DM) substantially influences the overall well-being and quality of life of individuals with diabetes and is widely associated with psychosocial burden. However, existing qualitative literature has largely focused on general adult populations, with limited attention to how illness experiences are shaped by gender and life-stage, particularly among midlife women in the UK. Moreover, the ways in which T2DM is integrated into identity, relationships, and future orientation during midlife remain insufficiently theorised. This study aimed to generate an in-depth, interpretive understanding of how midlife women with T2DM experience and make sense of the psychosocial, emotional, and self-management dimensions of the condition in their everyday lives. Methods A qualitative study using online semi-structured interviews. Participants were recruited through a national social media campaign and an established research engagement database. Interviews were conducted with 13 midlife women with type 2 diabetes. Data were analysed using reflexive thematic analysis within an interpretivist framework. Results The main four themes identified were Living with Type 2 Diabetes: encapsulates the practical aspects of living with diabetes, psychosocial dimensions: explores the broader impact of diabetes on participants’ lives, healthcare and support: sources for managing diabetes effectively and lastly outlook and personal development: captures participants’ perspectives on their treatment, their worries about the future, and the unexpected positive outcomes of living with diabetes. Together, these themes illustrate a dynamic process through which participants actively negotiate, reinterpret, and integrate T2DM within the context of midlife transitions, highlighting the interplay between illness, identity, and social roles. Conclusion The findings highlight the need for a multifaceted approach to addressing the barriers and facilitators of diabetes care. This study extends existing qualitative literature by offering a life-stage- and gender-sensitive conceptualisation of living with T2DM, emphasising midlife as a critical period of identity renegotiation and future reorientation. By incorporating patients’ perspectives into care, they may enhance diabetes self-management and support more responsive, person-centred interventions, ultimately improving long-term well-being.